Feasibility Study of Legen Drinks in Gresik Regency - Musarofah, Fitriatul; Pambudiarto, Benny Arif (PT FORMOSA CENDEKIA GLOBAL, 2024)
Gresik Regency, as a region producing siwalan trees, produces legen from the sweet liquid of siwalan flowers. Legen drinks require standards to ensure cleanliness, safety and suitability for consumption according to BPOM standards. 10 samples of legen drinks were tested for alcohol content using the dichromatometry method, showing that the alcohol content of fermented legen ranged from 4.96%-17.62%, still within safe and halal limits for consumption according to Food and Drug Control Standards Number 14 of 2016. Total Plate Results Count (TPC) shows that of the 10 samples tested, there were 2 samples that did not meet the requirements, having colony counts of 53,999 × 10-3 cfu/ml and 34,497 × 10-3 cfu/ml. In accordance with Food and Drug Control Standards Number 13 of 2019 regarding the maximum limit for fruit juice of 1 x 104 cfu/ml. That the microbiological and physical quality of Legen drinks in Gresik Regency does not always meet the safety standards of BPOM RI regulations.